2006
DOI: 10.1377/hlthaff.25.6.1688
|View full text |Cite
|
Sign up to set email alerts
|

Out-Of-Pocket Health Spending And The Rural Underinsured

Abstract: Multiple studies have documented higher uninsurance rates among rural compared to urban residents, yet the relative adequacy of coverage among rural residents with private health insurance remains unclear. This study estimates underinsurance rates among privately insured rural residents (both adjacent and nonadjacent to urban areas) and the characteristics associated with rural underinsurance. We found that 6 percent of privately insured urban residents were underinsured; the rate increased to 10 percent for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 7 publications
2
36
1
Order By: Relevance
“…Our finding of the percentage of underinsured is much higher than estimates of 7% to 12% found in national samples of nonelderly adults, 6,7 and higher than the 4.5% estimate for Colorado in 1995. 3 The definition used in this study was based on experiential criteria as opposed to financial criteria used in many other studies.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Our finding of the percentage of underinsured is much higher than estimates of 7% to 12% found in national samples of nonelderly adults, 6,7 and higher than the 4.5% estimate for Colorado in 1995. 3 The definition used in this study was based on experiential criteria as opposed to financial criteria used in many other studies.…”
Section: Discussioncontrasting
confidence: 81%
“…Those who spend more than 10% of their income on health care, or 5% for those below 200% of the federal poverty level, are considered to be underinsured. [3][4][5][6] Other studies have defined underinsurance based on patient's self-reported experience about being unable to afford recommended health care despite having insurance; it may not necessarily be related to their income. 7,8 This study follows this experiential definition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Still, these factors merit discussion here because they are key elements to the concept of underinsurance, even as their practical application will be much less in the future. "percentage of household income" marker that accounts for the fact that lower-income families are unable to divert resources to cover their health-related expenses (1,13,14,28,29,38).…”
Section: Economic Factorsmentioning
confidence: 99%
“…[3][4][5] Increasing coverage for adults through Medicaid expansions is thought to be a way of improving adequacy of coverage. 2 However, considerably less attention has been paid to underinsurance among low-income adults, 2,[5][6][7] especially those with public insurance. While underinsurance has been examined among children in public programs, 8 previous research has not explored the possibility that adults in Medicaid might be underinsured.…”
Section: Introductionmentioning
confidence: 99%